Análisis comparativo de la exportaciones no petroleras tradicionales en el periodo 2020-2022 - Quinto Yagual, Betsy Melissa (2024)
The exports of traditional non-oil products have faced distribution challenges, resulting in significant fluctuations in recent years. Therefore, the objective of this research was to conduct a comparative analysis of Ecuador's traditional non-oil exports, considering the periods 2020-2022. The methodology applied was of a mixed approach, as it was carried out based on statistical data provided by reliable sources such as the Central Bank of Ecuador, Ministries of Agriculture, Livestock and Fisheries, National Aquaculture Chamber, and the Fisheries Chamber, among others. The results obtained showed that shrimp had the highest incidence in Ecuadorian exports, followed by bananas, although with a decreasing trend, and cocoa, which showed recovery and growth. Tuna and fish exhibited relative stability, while coffee showed sustained growth, reflecting a diversified and evolving landscape for Ecuador's traditional non-oil exports. The main factors faced in their participation were health measure restrictions and political conflicts. Currently, exports of Ecuador's traditional products have become the country's main source of income. They generate foreign exchange that contributes to socioeconomic development and significantly impacts the trade balance, positioning Ecuador as one of the leading countries in Latin America contributing to commercial interaction with the rest of the world.